Research progress in high temperature functional coatings for advanced aeroengines - WANG Yidan; GUO Qian; ZHOU Qijie; ZHANG Chenyu; SONG Bingru; QIAO Jiao; FAN Dongyuan; HE Jian; HE Wenting; GUO Hongbo; GONG Shengkai; XU Huibin (Journal of Aeronautical Materials, 2024)
The aircraft engine is considered the “heart” of the aircraft. The development of advanced aircraft engines focuses on achieving a high thrust-to-weight ratio，high efficiency，low fuel consumption，and extended operational life. High-temperature functional coatings，such as thermal barrier coatings（TBCs），thermal/environmental barrier composite coatings（T/EBCs），and high-temperature stealth coatings，are applied to critical hot-end components of aircraft engines. These coatings play a significant role in enhancing the service performance，operational life，safety and reliability of the engine. Taking TBCs，T/EBCs，and high-temperature stealth coatings as examples，this paper provides a systematic overview of recent research progress in the design of high-temperature functional coating materials，coating preparation science and technology，and coating performance evaluation and characterization，both domestically and internationally，with a specific focus on the advancements made at Beihang University. Furthermore，challenges and development trends faced by new high-temperature functional coatings of advanced aircraft engines in the future are also discussed. In the future，the research focus of advanced high-temperature functional coatings will shift toward multifunctional composite coatings，enhanced adaptability to extreme environments，and improved process compatibility.